The impact of whole human blood on the kinetic inertness of platinum(iv) prodrugs – an HPLC-ICP-MS study - Theiner, Sarah (Dalton Trans, 2018)
The potential advantage of platinum(iv) complexes as alternatives to classical platinum(ii)-based drugs relies on their kinetic stability in the body before reaching the tumor site and on their activation by reduction inside cancer cells. In this study, an analytical workflow has been developed to investigate the reductive biotransformation and kinetic inertness of platinum(iv) prodrugs comprising different ligand coordination spheres (respectively, lipophilicity and redox behavior) in whole human blood. The distribution of platinum(iv) complexes in blood pellets and plasma was determined by inductively coupled plasma-mass spectrometry (ICP-MS) after microwave digestion. An analytical approach based on reversed-phase (RP)-ICP-MS was used to monitor the parent compound and the formation of metabolites using two different extraction procedures. The ligand coordination sphere of the platinum(iv) complexes had a significant impact on their accumulation in red blood cells and on their degree of kinetic inertness in whole human blood. The most lipophilic platinum(iv) compound featuring equatorial chlorido ligands showed a pronounced penetration into blood cells and a rapid reductive biotransformation. In contrast, the more hydrophilic platinum(iv) complexes with a carboplatin- and oxaliplatin-core exerted kinetic inertness on a pharmacologically relevant time scale with notable amounts of the compound accumulated in the plasma fraction.